STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN BUDAYA MUTU DI MADRASAH ALIYAH AMANATUL UMMA - Fitriyanti, Estika; Soedjarwo, Soedjarwo; Sholeh, Muhamad (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Madrasah Aliyah Amanatul Ummah is a modern religion-based school and has a curriculum that is integrated with Cairo, Egypt. The aim of this research is to see the role and obstacles of school principals as managers, supervisors, educators, administrators, leaders, work climate creators, entrepreneurs in improving the quality culture of madrasas. This research used a qualitative case study method. Data collection techniques used were interviews, observation and documentation studies. The subjects in this research were the principal, deputy principal, teachers and parents. Data analysis techniques with data condensation, data presentation, and data collection are displayed. The results of this research have two main themes, namely the Principal's Strategy in improving a quality culture and barriers to implementing a quality culture. The principal's strategies include improving quality, new adaptations, awareness of the implementation of quality culture in schools, quality of graduates, improving quality, developing human resource potential, the role of leaders, creating a positive environment, effective communication, forming a positive stigma in society, targets that need to be realized, encourage increased performance and capability of HR, stakeholder involvement. The obstacle to implementing a quality culture is that busy teaching hours can affect performance and quality so that countermeasures are needed to adjust mentoring time. School Principal Strategy As a leader, it is very necessary to properly manage human resources and natural resources to improve the quality of the school.